ICT TOOLS FOR SUPPORT OF STUDENTS’ INDIVIDUAL WORK IN THE STUDY OF QUANTUM PHYSICS - Stepan P. Velychko (Інформаційні технології і засоби навчання, 2018)
The introduction of modern innovative training technologies in the training of highly skilled specialists involves a significant expansion and increase of the significance of cognitive activity in the educational process of each student, and in particular his individual activity during the implementation of a laboratory practice on the course of general physics, including the study of the section "Quantum Physics". Our scientific researches convincingly prove the expediency of widespread use of computer-oriented means for the purpose of development of independent activity of students in physics and in their high efficiency in solving the problem of integration of the real and virtual experiment from the given section. For this purpose, our computer-oriented training tools and corresponding software products take into account the obligatory availability of successive modules that provide the multifunctionality of the proposed training kit for the physical workshop and practical training tasks from the corresponding section as autonomously (independently of others), for example and integrated with other modules. The isolated modules, on the one hand, are consistent with the types of educational activity of the student, and on the other hand, they contribute to the purposeful management of research work during the physical practice and thus are an important factor in the organization and management of the student's independent work. Such a technique allows the student to attain a sufficiently high level of understanding of each module and, accordingly, at the appropriate level, to master laboratory research on quantum physics, where the subject of study can be presented real or virtual, which simultaneously enhances the professional expertise of future physics teachers and professionals whose activities are " with physics, and also improves the efficiency of independent work of a future specialist.